Development of an Integrated PjBL E-Module on the Character of Kayuh Baimbai and the SETS Approach to Training Science Literacy - Nurul Hikmah; Mustika Wati; Dewi Dewantara; Sri Hartini (Jurnal Ilmiah Pendidikan Fisika, 2026)
The low level of students’ science literacy, as reported in the 2022 Programme for International Student Assessment (PISA), remains a major challenge in physics education. This study aimed to determine the validity of a Project-Based Learning (PjBL) e-module integrated with Kayuh Baimbai character values and the Science, Environment, Technology, and Society (SETS) approach to support the development of students’ science literacy. This study employed a research and development design using the ADDIE model, focusing on the development and validation stages. The research subjects consisted of 54 eleventh-grade students from SMAN in Banjarmasin, divided into an experimental class and a control class, each comprising 27 students. The research instruments included validation sheets used to evaluate the developed products, namely the e-module, teaching materials, student worksheets, and learning achievement tests. The level of validity was analyzed using the average validator scores, while reliability was determined using Cronbach’s alpha coefficient. The results indicated that all developed learning components achieved the “very valid” category, suggesting that the e-module was suitable for use in physics learning. The integration of local wisdom through Kayuh Baimbai character values with the SETS approach represents an innovative contribution to the development of culturally relevant digital learning materials to support students’ science literacy.